2017
DOI: 10.1111/jph.12582
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of yield losses caused by leaf anthracnose on sorghum in Brazil

Abstract: The leaf anthracnose disease in sorghum, caused by Colletotrichum sublineolum (Henn. ex Sacc. & Trotter), is widely distributed throughout its Brazilian cultivation areas. The disease can cause significant losses in grain yield and quality. This study aimed to quantify the effects of leaf anthracnose on grain yield of different sorghum genotypes. Two elite inbred lines of sorghum, BR009 (susceptible) and BR008 (moderately resistant), and the hybrids, BR304 and MR43 (susceptible), BRS310 and DKB599 (moderately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Exploiting genetic resistance is an economical and efficient strategy to manage pests and diseases. Sorghum anthracnose, caused by Colletotrichum sublineolum, may reduce crop yielding up to 86% (Cota et al, 2017), and due to high pathogen variability, developing genetic resistance is challenging (Xavier et al, 2018). Mehta et al (2005) and Costa et al (2011) identified vertical resistance to specific races of Colletotrichum sublineolum.…”
Section: A Brief History Of Sorghum Breeding In Brazilmentioning
confidence: 99%
“…Exploiting genetic resistance is an economical and efficient strategy to manage pests and diseases. Sorghum anthracnose, caused by Colletotrichum sublineolum, may reduce crop yielding up to 86% (Cota et al, 2017), and due to high pathogen variability, developing genetic resistance is challenging (Xavier et al, 2018). Mehta et al (2005) and Costa et al (2011) identified vertical resistance to specific races of Colletotrichum sublineolum.…”
Section: A Brief History Of Sorghum Breeding In Brazilmentioning
confidence: 99%
“…ture food stability, especially in resource-poor drier agro-ecological regions [1] [2] [3]. This versatile drought-tolerant crop will continue to gain in importance for its varied uses as the environment becomes less predictable due to climate change and those looking for healthy diet options [2] [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Acharya et al [10] reported that for every percent increase in sorghum anthracnose severity, 27 to 85 kg/ha losses in grain yield could be expected. In Brazil, 86% yield loss was measured on BR009 when the level of anthracnose severity on the genotype reached 100% [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…& Trotter) [ 7 ], is one of the most devastating diseases of the crop. Grain yield losses ranging from 36% in susceptible genotypes of sorghum [ 8 ] to as high as 86% in an inbred line under maximum disease severity were reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%